Overexpression of a Plasma Membrane-Localized SbSRP-Like Protein Enhances Salinity and Osmotic Stress Tolerance in Transgenic Tobacco - Udawat, Pushpika; Jha, Rajesh K.; Mishra, Avinash; Jha, Bhavanath (Frontiers in Plant Science, 2017)
An obligate halophyte, Salicornia brachiata grows in salt marshes and is considered to be a potential resource of salt- and drought-responsive genes. It is important to develop an understanding of the mechanisms behind enhanced salt tolerance. To increase this understanding, a novel SbSRP gene was cloned, characterized, over-expressed and functionally validated in the model plant Nicotiana tabacum. The genome of the halophyte S. brachiata contains two homologs of an intronless SbSRP gene of 1262 bp in length that encodes for a stress-related protein. An in vivo localization study confirmed that SbSRP is localized on the plasma membrane. Transgenic tobacco plants (T1) that constitutively over-express the SbSRP gene showed improved salinity and osmotic stress tolerance. In comparison to Wild Type (WT) and Vector Control (VC) plants, transgenic lines showed elevated relative water and chlorophyll content, lower malondialdehyde content, lower electrolyte leakage and higher accumulation of proline, free amino acids, sugars, polyphenols and starch under abiotic stress treatments. Furthermore, a lower build-up of H2O2 content and superoxide-radicals was found in transgenic lines compared to WT and VC plants under stress conditions. Transcript expression of Nt-APX (ascorbate peroxidase), Nt-CAT (catalase), Nt-SOD (superoxide dismutase), Nt-DREB (dehydration responsive element binding factor) and Nt-AP2 (apetala2) genes was higher in transgenic lines under stress compared to WT and VC plants. The results suggested that overexpression of membrane-localized SbSRP mitigates salt and osmotic stress in the transgenic tobacco plant. It was hypothesized that SbSRP can be a transporter protein to transmit the environmental stimuli downward through the plasma membrane. However, a detailed study is required to ascertain its exact role in the abiotic stress tolerance mechanism. Overall, SbSRP is a potential candidate to be used for engineering salt and osmotic tolerance in crops.